Numerical modelling of bearing strength of concrete strengthening with carbon fibre reinforced polymers (CFRP) wrapping for different thickness of CFRP Sheet / Filzah Sofiya Kamaruzaman and Norrul Azmi Yahya - Kamaruzaman, Filzah Sofiya; Yahya, Norrul Azmi (2024)
The bearing strength of concrete plays an important role in transmitting the bearing force into the structural supports, especially for buildings and infrastructure such as concrete footings, concrete bridges, column corbels and concrete connections. The structural behaviour of the concrete bearing is related to the confinement effect, in which the load is transmitted to the concrete surface through the contact interaction between the steel bearing plate. However, extreme penetration on the contact surface of the concrete blocks by the steel bearing plate leads to failure modes on the concrete block. This research study focuses on the performance of the bearing strength of the concrete when it is wrapped with carbon fiber-reinforced polymers (CFRP) as the strengthening method. This research also examines the bearing strength of concrete when it is wrapped with a single layer of different thicknesses of CFRP sheet, which range from 1mm to 4mm thick. In order to understand the concrete bearing performance, a finite element model (FEM) using ABAQUS/CAE software is developed. An optimum meshing with a size 12.5mm is used for the further nonlinear analysis of the concrete model to discuss the results, such as the model validation by comparing the bearing strength results from the FE model with the Australian Standard, the comparison of the load-displacement curve for different thicknesses of CFRP wrapping, as well as the structural response or visualization of the concrete model. From the results, it shows that the different thicknesses of the CFRP wrapping significantly have a positive impact on the bearing capacity of the concrete, where the bearing strength of the concrete increases up to 26.16% as the thickness of the CFRP wrapping increases to 4mm for the optimum meshing size of 12.5mm. The FE visualization also shows various structural responses of the concrete bearing in the context of the deformation shape, vertical displacement, vertical stress distribution and max and minimum principal stress distribution of the concrete bearing, which are further discussed in this report.